Software Architecture Hour with Neal Ford. (O'Reilly Media, Inc., 2023)
Join us for a special conversation with Neal Ford and Kent Beck, programmer, creator of Extreme Programming, pioneer of software patterns, coauthor of JUnit, rediscoverer of test-driven development, and signer of the Agile Manifesto. They'll discuss how software design is an exercise in human relations, then get into the work Kent is doing to empower geeks everywhere to improve software design, starting with making small changes to code (tidyings) before moving into changes that improve the larger design. Along the way, they'll dive into the theory behind software design (coupling, cohesion, discounted cash flows, and optionality). This is a chance for you to hear from Neal and Kent about software, architecture, and their own career journeys. They'll spend a few minutes covering the trends that are influencing architecture, then tell you what you need to know to stay ahead of the curve. What you'll learn and how you can apply it Learn how to craft technical strategy and make sure it's aligned to business needs See what's coming next with software architecture This recording of a live event is for you because... You want the chance to hear from Neal Ford and Kent Beck about software design, Extreme Programming, and what the future might look like. You're looking for ways to grow your own skills and to act as an innovator in your organization. Recommended follow-up: Read Extreme Programming Explained, second edition (book) Read Test-Driven Development by Example (book) Read Implementation Patterns (book).